Validity and Effectiveness of E-Module-Based Learning Media in Informatics Subjects - Dimi Oksila; Giatman; Dedy Irfan; Khofifah Alawyah (Jurnal Penelitian Pendidikan IPA, 2025)
Understanding programming algorithms, is a basic competency that must be mastered by high school students in informatics subjects. However, students have difficulty in mastering programming algorithm material as seen by the learning outcomes of students who are still below the KKM, the use of learning media is still conventional (ordinary printed books, whiteboards, limited teaching modules, LCD projectors as well as power points). This research uses the Research and Development (R&D) research method with the 4D development model which consists of 4 stages, namely define, design, development, and disseminate. The data analysis technique used is descriptive data analysis to describe the validity, practicality, and effectiveness of the developed learning media. The results of this development research are informatics e-modules. The results of feasibility validity media experts in the very feasible category, the results of feasibility validity material experts in the very feasible category, the results of practicality teachers in the very practical category, the results of practicality testing by students in the very practical category, and the results of Paired Samples Test testing obtained data Sig < 0.005 (0.001 < 0.005), Tcount > Ttable (3.734 > 20.040) means effective, so this media is valid, practical, and effective to use as learning media.